Balzac and Tocqueville: the social change in revolutionary France - Cordeiro, Sara Ramos (2007)
This essay intends to broach, respectively, the artistic and intellectual production of Honore de Balzac and Alexis de Tocqueville, related to social and historical reality in which both authors produced their works. In dealing with two great names from the French intellectuality, whose works dimensions are beyond the limits of a text with this nature, we intend to indicate, by means of suggestion, some relevant proximity aspects inside these authors thoughts, concerning to the social change in France in the revolutionary period (1789-1848).